A Versatile Hermetically Sealed Microelectronic Implant for Peripheral Nerve Stimulation Applications - Jiang, Dai; Liu, Fangqi; Lancashire, Henry T.; Perkins, Timothy A.; Schormans, Matthew; Vanhoestenberghe, Anne; Donaldson, Nicholas De N.; Demosthenous, Andreas (Frontiers in Neuroscience, 2021)
This paper presents a versatile neurostimulation platform featuring a fully implantable multi-channel neural stimulator for chronic experimental studies with freely moving large animal models involving peripheral nerves. The implant is hermetically sealed in a ceramic enclosure and encapsulated in medical grade silicone rubber, and then underwent active tests at accelerated ageing conditions at 100 °C for 15 consecutive days. The stimulator microelectronics are implemented in a 0.6-µm CMOS technology, with a crosstalk reduction scheme to minimize cross-channel interference, and high-speed power and data telemetry for battery-less operation. A wearable transmitter equipped with a Bluetooth Low Energy radio link, and a custom graphical user interface provide real-time, remotely controlled stimulation. Three parallel stimulators provide independent stimulation on 3 channels, where each stimulator supports 6 stimulating sites and 2 return sites through multiplexing, hence the implant can facilitate stimulation at up to 36 different electrode pairs. The design of the electronics, method of hermetic packaging and electrical performance as well as in vitro testing with electrodes in saline are presented.